Islam, Politik, dan Demokrasi di Asia Tenggara: Sebuah Pengamatan Awal tentang Konteks dan Praktik Moderasi Agama - Gutomo Bayu Aji; Mulawarman Hannase (LIPI Press, 2022)
Post-colonial states in Southeast Asia have deep roots in their history of civilization and culture. Its strength lies not in its purity of identity but in its ability to be a hybrid of the various waves of civilization and culture that make it cosmopolitan. This character becomes the basis for analyzing the ability of post-colonial states to accommodate religion, especially the strengthening of Islamism throughout the formation of the nation-state. This article puts the experience of moderating the threat of disintegration in that capability. The question to be answered is how do these states moderate the threat of disintegration related to the strengthening of Islamism? Through literature study, it can be seen that there are three threats of disintegration related to Islamism, namely first, the struggle for territorial sovereignty in Thailand and the Philippines; second, the movement with the vision of an Islamic state in Indonesia; and third, the establishment of the Jamaah Islamiyah caliphate covering Thailand, Malaysia, Singapore, Indonesia, Brunei Darussalam and the Philippines. The ability to accommodate through religious moderation occurs in three complex political and democratic processes. First, moderation through the process of integration of the nation-state as in Singapore, Thailand and the Philippines; Second, moderation through the democratization process in almost all countries in the archipelagic region; and third, moderation by civil society in Indonesia and Malaysia. Nevertheless, the challenges of Islamism, especially those related to the network of transnational Islamic ideologies, still haunt states in Southeast Asia. This article suggests that the government and civil society work together to increase the state's role in religious moderation capabilities that are in line with global dynamics.